PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) PADA BERBAGAI PEMUPUKAN DAN URINE SAPI: GROWTH OF ARABICA COFFEE SEEDS (Coffea arabica L.) ON VARIOUS FERTILIZATION AND COW URINE - Purwati; Yetti Elidar (Universitas Widya Gama Mahakam, 2021)
Seedling on Arabica coffee plants (Coffea Arabica L.) is a stage that will determine plant productivity in the field, therefore it needs to be supported by quality seeds (superior seeds), resistant to pests and diseases and response to fertilization. So it is necessary to do research on the growth of coffee seedlings on various fertilizers and cow urine. This study aims to determine the number of fertilizers (SP-36, KCl, cow manure) and cow urine on the best growth of coffee seedlings in nurseries. The research was conducted at Sempaja Village, North Samarinda District and at the Agronomy Laboratory of Faperta Unmul Samarinda in 2017. This study consisted of 4 experiments where each experiments were arranged in a Completely Randomized Design (CRD) with 4x4 factorial experiments with two replications. The first experiment was the dose of SP-36 ) fertilizer (P) consisted of four levels, namely, 0 g polybag-1 , 5 g polybag-1 , 7 g polybag-1 , 9 g polybag-1 and cow urine concentration (S) consisted of four levels, namely, 0 mL L-1 , 250 mL L-1 , 300 mL L-1 , 350 mL L-1. The second experiment was the dose of KCl fertilizer (K) consisted of four levels, namely, 0 g polybag-1 , 4 g polybag-1 , 5 g polybag-1 , 6 g polybag-1 and cow urine concentration (S) consisted of four levels, namely, 0 mL L-1 , 150 mL L-1 , 200 mL L-1 , 250 mL L-1. The third experiment was the dose of cow manure (A) consisted of four levels, namely, 0 g polybag-1 , 250 g polybag-1 , 500 g polybag-1 , 750 g polybag-1 and cow urine concentration (S) consisted of four levels, namely, 0 mL L-1 , 75 mL L-1 , 150 mL L-1 , 225 mL L-1. Parameters observed in each study at four months after treatment included: increase in plant height, number of leaves and stem diameter, dry weight of plants, shoot dry weight, root dry weight and root crown ratio. Data were analyzed using variance and continued with the least significant difference test at 5% level. The results of the study on the application of various fertilizers (SP-36, KCl and cow manure) showed a very significantly difference to the increase in seedling height, number of leaves and stem diameter but not significantly different to plant dry weight, shoot dry weight, root weight and ratio root crown at three months after treatment. The application of cow manure can increase the yield of plant dry weight, shoot dry weight, root dry weight and root crown ratio. Meanwhile, the concentration of cow urine and the interaction between each fertilizer ( SP-36, KCl and cow manure) and the concentration of cow urine were not significantly different for all parameters. Giving cow urine can increase the yield of plant dry weight, shoot dry weight, root dry weight and root crown ratio.